Dynamic Impact Factor and Resonance Analysis of Curved Intercity Railway Viaduct - Jun Wang; Chenxing Cui; Xiang Liu; Mingjie Wang (Applied Sciences, 2022)
A viaduct is an important structural form in intercity railway networks, and the curved bridge is inevitable in railway line network planning. When the vehicles cross through the curved bridge, the transverse load experienced by the bridge is much larger than that of the straight bridge due to the centrifugal forces. Therefore, in the bridge resonance analysis, in addition to the vertical moving vehicle load, it is also imperative to consider the radial vehicle load. In order to systematically analyze the dynamic impact factor (or dynamic load allowance) and resonance conditions of the curved intercity railway viaduct, a numerical model is developed. The reliability of the proposed model is assessed by comparing it with the existing literature. Taking the curved viaduct of Zhengzhou-Xuchang railway as a case study, the theoretical resonance velocity, dynamic impact factor, and dynamic time-history response under resonance velocity are calculated. The parameters of different spans, curve radius, and speeds are analyzed, and the reasonable ranges of bridge natural vibration frequency are determined.